Jackand the Beanstalk - Burgaud Tatsiana (Swindon, UK Child's Play (International) Ltd, 2023)
Much-loved fairy tales leap to life in this series of lively retellings. There's a surprise under each lift-up flap to add to the fun!
Keywords: children story